Mapping the Research Landscape on Leadership and Communication in Indonesia: A Bibliometric Analysis - Muhamad Bagas Firmansyah; Aniek Rumijati; Uci Yuliati (Jurnal Warta Dharmawangsa, 2026)
This study maps the research landscape on leadership and communication in Indonesia from 2020 to 2025 using bibliometric analysis. Data were retrieved from the Scopus database and examined through VOSviewer and Biblioshiny to identify publication trends, thematic structures, and collaboration patterns. The findings reveal a steady growth in scholarly output, with research predominantly situated in the social sciences, business, and public health domains. Thematic analysis highlights several major clusters, including leadership and governance in health settings, transformational leadership and organizational culture, digital leadership and knowledge management, human resource development, and leadership in higher education. Co-authorship visualization indicates the presence of active research groups, though collaboration across clusters remains limited. These results demonstrate that leadership and communication scholarship in Indonesia increasingly intersects with crisis management, digitalization, and organizational performance. The study contributes to a deeper understanding of conceptual development, key contributors, and emerging research directions, providing valuable insights for future academic inquiry and policy formulation.